Integrasi Teknologi Digital Sebagai Strategi Peningkatan Nilai dan Produktivitas Bisnis di Era Modern - Fauzy Imam Syah; Muhammad Irwan Padli Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This article examines the role of digital technology integration as a strategic approach to enhancing operational productivity and creating sustainable business value in the modern era. Amid rapid digital transformation, technologies such as cloud computing, artificial intelligence, IoT, and data analytics not only automate routine processes but also enable service personalization, business model innovation, and real- time data-driven decision-making. Through a literature review and conceptual analysis, this study demonstrates that successful technology integration depends on alignment with core business strategy, human capital readiness, and commitment to ethical and sustainable data governance. Challenges including digital skills gaps, organizational resistance, and system fragmentation must be addressed through a holistic approach. The findings affirm that effective digital transformation is not merely about adopting tools, but about fundamentally reshaping organizational culture and strategy to deliver long-term value in an increasingly dynamic and competitive landscape.